A study on the factors that influence the usage of credit card: case in Kelantan / Nur Fadhilah Ismail - Ismail, Nur Fadhilah (2011)
Nowadays, credit card ownership has spread widely among people. The spread of credit cards usage has results an increasing number of debts in this developing nation. A study has been carried out in order to examine the factors that influence the credit cards usage especially among Kelantanese, as well as to measure the attribute towards the personal attitude or behaviour of consumers on the credit card usage. The researcher also wants to measure the effect of consumer’ attitudes toward credit card debt. Thus, the researcher had looked for the factors that influence the usage of credit cards among consumers and focus on the specific areas. By using the specific research method, the researcher has collected and gathered the information on the factors that influence the usage of credit card as well as, the pattern of credit card users’ behaviour usage. Furthermore, the researcher also needs to know the effect of the consumer’s behaviour towards the excessive credit card usage. There are 100 questionnaires were distributed in Kota Bharu, Kelantan in order to collect the data